The Relationship between ABO Blood Group and Glioblastoma Multiforme - Zeki Akca; Hasan Mutlu; Abdulsamet Erden; Abdullah Buyukcelik; Emel Yaman Sezer; Ali Inal (Medicine Science, 2014)
Glioblastoma Multiforme (GBM) is the most common type of primary brain tumor and its prognosis is poor. Some studies have investigated the relationship between ABO Blood Groups and cancer risk. In this study we evaluated the patients with GBM and control group regarding ABO Blood Groups. Secondly we compared the progression free survival (PFS) and overall survival (OS) regarding ABO Blood Group in patients with GBM. A total of 72 patients with GBM were enrolled from Mersin Government Hospital, Acibadem Kayseri Hospital and Kayseri Training and Research Hospital between 2006-2012. Healthy donors that were admitted to the Turkish Red Crescent Blood Service in our city in year 2012 were selected as control group. Both of groups were compared regarding ABO Blood Groups. The PFS and OS were evaluated according to ABO Blood Groups in patients with GBM. We did not find any significant difference regarding the ratio of ABO Blood Groups between patients with GBM and control group. And there were no significant difference for PFS and OS among O, A, B, AB groups in patients with GBM. According to our results, comparison of control group with healthy donors and GBM patients, the ratio of blood groups was similar in both. And ABO Blood Groups have no effect on PFS and OS in patients with GBM. Also further studies are needed to explain whether there is any relationship between ABO Blood Group and Glioblastoma Multiforme. [Med-Science 2014; 3(4.000): 1639-47]